EASTERN RELIGIONS AND WESTERN THOUGHT - RADHAKRISHNAN S (OXFORD UNIVERSITY PRESS, 2005)
"HINDU PHILOSOPHY, SOUL, BRAHMAN, MYSTICISM, ETHICS, COMPARATIVE RELIGION, EASTERN RELIGIONS, WESTERN THOU"
Keywords: EASTERN RELIGIONS AND WESTERN THOUGHT